OTOMATISASI SISTEM PRODUK DALAM PENGOLAHAN DATA PADA PROSES HIRING DI PT.PERTAMINA (PERSERO) - Frieyadie, Frieyadie; Faldanu, Chaidir Rahman (Jurnal Pilar Nusa Mandiri, 2019)
One month hiring process of new workers if taken on average reaches 250-300 people, which consists of fresh graduates, experience and shipping workers (Ships). The hiring process is still done manually input into the system, so it is quite a lot of spending and human resources (HR). Reporting data and presenting data related to business processes within the company also need to be made better and informative. Therefore it is necessary to automate the system to be able to support the speed and accuracy in the hiring process. Automation is the initial general form of organizational change in the form of a tool for ease of daily work. The method used to answer, uses the TAM method. The purpose of this research is to find out how much automation on the SAP system can have an effect on working time, which is more than 8 hours a day so that excessive overtime occurs, to find out the system automation in SAP is able to efficiently process data recording that occurs repeatedly and to find out the system automation in SAP can reduce human error. The level of acceptance of SAP users towards Hiring Process Automation at PT. Pertamina (Persero) based on perceived usefulness, perceived ease of use, attitude toward using, behavioral intention to use and actual use as a whole reached 87.74%, included in the category of strongly agree.